APLIKASI MEMBRANE BIOREACTOR (MBR) UNTUK PROSES DAUR ULANG AIR LIMBAH - Hernaningsih, Taty (Center for Environmental Technology, 2014)
The population is growing rapidly result to increased demand for drinking water while the other side of this situation causes to the increasing amount of wastewater. Waste water treatment plant has been built in several major cities in Indonesia to overcome the problem of pollution.Ã‚Â Wastewater treatment plant only treats wastewater to tackle environmental pollution without being able to overcome the shortage of clean water community. Therefore, to solve the existing problems will be considered any further processing with recycled waste water treatment. One technology that may be developed for this purpose is the system of Membrane Bioreactor (MBR). This has been widely applied as an advanced unit of wastewater treatment and serves as a unit of processing recycled waste water. The MBR system has advantages such as: it only takes a little bit of land, can treat wastewater with discharge varying quality and process wastewater with high pollutant removal efficiency. MBR were investigated using a membrane filter submerged in the reactor. Membrane module is hollow fiber with a form of polymeric membrane materials. Research has been done on wastewater treatment with a combination of conventional WWTP as preliminary and advanced processing unit with MBR since March 4, 2014 until June 2014. The effluent qualityÃ‚Â of result research proved thatÃ‚Â the treated water quality meetsÃ‚Â water quality standards are set withÃ‚Â Permenkes RI N0.416/Menkes/Per/IX/1990, dated 3 September 1990. The nitrification and denitrification also proceed well so that the concentration of nitrite and nitrate meet the quality standards. In addition, the percentage removal of heavy metals (arsenic, cadmium, chromium, selenium, lead) can reach 99%.Ã‚Â Keywords: MBR, wastewater reuse, BOD5, COD, HRT dan SRT